1997
DOI: 10.1111/j.1749-7345.1997.tb00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Different Sized Wild and Pond‐reared Penaeus paulensis Females

Abstract: The present study analyzes the reproductive performance of three size classes of wild (average weight of 46.5, 55.0, and 63.2 g) and three size classes of pond‐reared (18.4, 21.3, and 25.1 g) Penaeus paulensis females. Unilaterally eyestalk ablated females were placed for 70 d in 3.6 m diameter tanks at 6 individuals/m2 and a 1.2:1 female‐male ratio. Number of spawns, eggs, nauplii, fertilization and hatching rates were recorded every second day. The length of unfed protozoea I larvae was also recorded. Larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 14 publications
3
57
1
Order By: Relevance
“…The mean number of eggs per spawn was relatively low (16,000-40,000 eggs/spawn) compared with those usually obtained when larger maturation tanks are applied. Although the potential fecundity of P. paulensis reported by Iwai (1978) under field (Southeast Brazilian off-shore areas) was up to 500,000 eggs per spawn, when eyestalk ablated wild females were maintained in captivity for at least 45 days, the mean number of eggs per spawning event ranged from 16,000 to 160,000 (Marchiori and Boff, 1983;Cavalli et al, 1997;Cavalli et al, 1998), while the number of nauplii per spawn ranged from 60,000 to 140,000 (Beltrame and Andreatta, 1991;Marchiori and Cavalli, 1993;Vinatea et al, 1993;Petersen et al, 1996;Reis et al, 1998). In the present study, the number of eggs per spawning event was in agreement with those usually observed for wild broodstock maintained in larger circular tanks, but again a relative decrease was observed in the number of eggs per spawn in this tank shape/size.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The mean number of eggs per spawn was relatively low (16,000-40,000 eggs/spawn) compared with those usually obtained when larger maturation tanks are applied. Although the potential fecundity of P. paulensis reported by Iwai (1978) under field (Southeast Brazilian off-shore areas) was up to 500,000 eggs per spawn, when eyestalk ablated wild females were maintained in captivity for at least 45 days, the mean number of eggs per spawning event ranged from 16,000 to 160,000 (Marchiori and Boff, 1983;Cavalli et al, 1997;Cavalli et al, 1998), while the number of nauplii per spawn ranged from 60,000 to 140,000 (Beltrame and Andreatta, 1991;Marchiori and Cavalli, 1993;Vinatea et al, 1993;Petersen et al, 1996;Reis et al, 1998). In the present study, the number of eggs per spawning event was in agreement with those usually observed for wild broodstock maintained in larger circular tanks, but again a relative decrease was observed in the number of eggs per spawn in this tank shape/size.…”
Section: Discussionmentioning
confidence: 98%
“…It is, therefore, possible to speculate that the number of eggs per spawn may be reduced in smaller maturation tanks. The reproductive performance traits could be affected by many factors such as different species, broodstock source and size Cavalli et al, 1997;Palacios et al, 1999), nutrition (Harrison, 1990;Sangpradub et al, 1994), genetics (Benzie, 1997;Benzie, 1998) and environmental conditions (Hansford and Marsden, 1995;Crocos and Coman, 1997). Therefore, these findings must be considered to compare reproductive performance reported in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as there is a comprehensive knowledge of the biology and culture of F. paulensis, it is possible to produce large numbers of PL from either wild (Marchiori and Boff, 1983;Marchiori and Cavalli, 1993;Marchiori, 1996) or domesticated broodstock (Cavalli et al, 1997;Peixoto et al, 2003aPeixoto et al, , 2004aPeixoto et al, , 2005. Since production has not yet reached a commercial scale, the laboratory PL provided to the fishermen were still produced at the university's Marine Aquaculture Centre and handed to the fishermen.…”
Section: Stocking Of Postlarvae and Culture Managementmentioning
confidence: 99%
“…Despite the supposedly advantageous performance of wild broodstock, the unpredictable supply and high capture costs might constrain the sustainable development of F. paulensis farming in the region. In this context, several studies have been carried out to optimize the maturation and reproduction of this species in captivity (Peixoto et al, 2002a(Peixoto et al, , 2002b(Peixoto et al, , 2003b(Peixoto et al, , 2003c(Peixoto et al, , 2004b, especially the evaluation of the domesticated broodstock as an alternative (Cavalli et al, 1997;Peixoto et al, 2003aPeixoto et al, , 2004a. The accelerated search to close the life cycle and improve the reproductive performance of F. paulensis in captivity will certainly contribute to the design of an efficient breeding program.…”
Section: Availability Of Plmentioning
confidence: 99%